Clean fuel engine valve seat ring and preparation method thereof, engine and automobile

By using cobalt-based alloy materials with Co and Mo contents limited to a reasonable range in the valve seat of the clean fuel engine, and using sintering and repressure shaping processes to form a cobalt-based-wear-resistant alloy phase, the problems of valve seat wear and seal failure are solved, and the high wear resistance and seal reliability of the valve seat are achieved.

CN119351889BActive Publication Date: 2025-04-22ZHEJIANG GEELY AUTOMOBILE ENGINEERING TECHNOLOGY DEVELOPMENT CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411924425.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-22
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

Clean fuel engine valve seats are prone to abnormal wear, excessive wear and leakage after long-term use, resulting in reduced seal reliability.

Method used

The cobalt-based alloy material containing Co and Mo is used to limit the total content of Co and Mo not exceeding 40% of the total content, and the total content of all heavy metal components except iron is limited to no more than 45% of the total content. The cobalt-based wear-resistant alloy phase is formed through sintering and re-pressure shaping processes to improve the wear resistance and sealing reliability of the valve seat.

Benefits of technology

It significantly improves the wear resistance and seal reliability of the valve seat, extends the service life of the valve seat, and meets the high sealability and wear resistance requirements of the clean fuel engine for the valve seat.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119351889B_ABST
    Figure CN119351889B_ABST
Patent Text Reader

Abstract

The present application provides a clean fuel engine valve seat insert and a preparation method thereof, an engine and a vehicle. The clean fuel engine valve seat insert includes the following chemical components in weight percentage: C: 0.65-1.15%, Co: 25-28%, Mo: 8-12%, Cr: 1.7-3.5%, W: 0.2-0.6%, V: 0.05-0.3%, Mn: 0.1-0.6%, S: 0.1-0.7%, Si: 0.7%-1.4%, Sn: 0.6-1.3%, impurities <5%, the balance is Fe, and Cu is not included. The clean fuel engine valve seat ring provided in the present application uses Co and Mo as two heavy metals as main components, limits the total content of Co and Mo to no more than 40% of the total content and no less than 33% of the total content, and limits the total content of all heavy metal components in the valve seat ring except iron to no more than 45% of the total content, thereby being able to produce a larger cobalt-based wear-resistant alloy phase, thereby improving the wear resistance of the valve seat ring and ensuring the sealing reliability of the valve seat ring.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of automobile technology, and in particular to a valve seat ring for a clean fuel engine and a preparation method thereof, an engine and an automobile. Background Art

[0002] The engine is the heart of the car, and engine performance is one of the key factors affecting the performance of the car. Among them, sealing technology is an important indicator for evaluating engine reliability, which directly affects the operation of the engine. As a key sealing component, the valve seat ring of the clean fuel engine has a great impact on the sealing reliability of the entire engine. The reason is that the product of methanol combustion is very clean, unlike ordinary gasoline, which will not produce carbon deposits attached to the sealing surface of the valve seat ring due to incomplete combustion, thereby buffering the valve seating process. In addition, since clean fuel itself is corrosive to a certain extent, it is easy to aggravate the wear of the valve seat ring during the operation of the engine. The use of conventional valve seat rings cannot resist the impact of the valve, and the seal fails.

[0003] With the promotion and application of clean fuel engines, the requirements for the wear resistance and corrosion resistance of valve seat alloy materials have been correspondingly improved, and at the same time, higher requirements have been put forward for the sealing reliability of valve seat alloys. At present, the conventional design of valve seat alloy materials is based on Fe powder, and metal powders such as Mn, Ni, Si and S are added. The valve seat is prepared by die pressing, sintering copper infiltration, deep cooling and tempering, cutting and oil immersion treatment. However, after the valve seat is installed in the clean fuel engine for a long time, it is easy to have abnormal wear, eccentric wear and leakage and other sealing failure problems, which reduces the sealing reliability of the valve seat. Summary of the invention

[0004] The present application provides a clean fuel engine valve seat ring and a preparation method thereof, an engine and a car, which can improve the wear resistance of the valve seat ring and ensure the sealing reliability of the valve seat ring.

[0005] Specifically, the present application is implemented through the following technical solutions:

[0006] In one aspect, the present application provides a valve seat insert for a clean fuel engine, wherein the clean fuel includes but is not limited to at least one of methanol, ethanol and hydrogen. The valve seat insert for the clean fuel engine includes the following chemical components in weight percentage:

[0007] C: 0.65~1.15%, Co: 25~28%, Mo: 8~12%, Cr: 1.7~3.5%, W: 0.2~0.6%, V: 0.05~0.3%, Mn: 0.1~0.6%, S: 0.1~0.7%, Si: 0.7%~1.4%, Sn: 0.6~1.3%, impurities <5%, the balance is Fe, and Cu is not included.

[0008] Clean fuel refers to fuel that does not emit pollutants and can be directly used in production and life. Taking ethanol fuel (E100) as an example, ethanol generates less oxides during the combustion process. Since the valve seat ring and the valve are in direct contact in most cases during engine operation, the valve seat ring mainly shows two forms of knock wear and adhesive wear under this condition. Among them, solving knock wear is the primary problem, and the most effective measure to solve knock wear is to increase hard particles, that is, to increase wear-resistant heavy metals. Although adding wear-resistant precious metals can improve the wear resistance of alloy materials, the applicant's research has found that the proportion of wear-resistant heavy metals generally cannot exceed 45% of the total amount of alloy materials. Once exceeded, the overall adhesion of the alloy material will be very poor, resulting in a significant decrease in mechanical properties.

[0009] Before the initial heating temperature of the alloy powder formed by heavy metal elements and non-metal elements reaches 912℃, the interstitial solid solution of carbon dissolved in the α-Fe (body-centered cubic structure) of the iron powder is called ferrite. As the temperature rises, the α-Fe (body-centered cubic structure) of the iron powder will transform into γ-Fe (face-centered cubic structure) to form austenite. Among them, the heavy metal element Co can be infinitely dissolved in γ-Fe, and its solubility in α-Fe is about 76%. Therefore, Co is used as a binder for cemented carbide, and the high-temperature alloy containing Co still has high strength and creep resistance at 900-1000℃. The heavy metal element Mo is often added to alloy materials as a wear-resistant heavy metal because of its high density, high strength, high melting point, high high-temperature strength and high-temperature hardness, small thermal expansion coefficient, stable chemical properties, strong corrosion resistance, good machinability and other excellent mechanical properties and other physical properties.

[0010] The above scheme uses Co and Mo as the main components, limits the total content of the two heavy metal components Co and Mo to no more than 40% of the total content and no less than 33% of the total content, and limits the total content of all heavy metal components in the valve seat ring except iron to no more than 45% of the total content, which can produce a larger cobalt-based wear-resistant alloy phase, thereby improving the wear resistance of the valve seat ring and ensuring the sealing reliability of the valve seat ring.

[0011] It should be noted that the above-mentioned "heavy metals" refer to metal elements with a density greater than 4.5g / cm³. In addition, the content of each chemical component in this article includes both the endpoint value of the content range and the middle value of the content range. For example, the content range of C is 0.65~1.15%, specifically 0.65%, 0.7%, 0.82%, 0.96%, 1.15%, but not limited to this.

[0012] In one embodiment, the clean fuel engine valve seat insert comprises the following chemical components in weight percentage:

[0013] C: 0.65~1.15%, Co: 26.5-27.5%, Mo: 9.5~10.5%, Cr: 3~3.5%, W: 0.4~0.6%, V: 0.1~0.2%, Mn: 0.4~0.6%, S: 0.1~0.7%, Si: 0.7%~1.4%, Sn: 0.6~1.3%, impurities <5%, the balance is Fe, and Cu is not included.

[0014] Exemplarily, the valve seat insert includes an intake valve seat insert and an exhaust valve seat insert, and at least one of the intake valve seat insert and the exhaust valve seat insert has the chemical composition of the above weight percentage.

[0015] In one embodiment, the valve seat insert is composed of a cobalt-based alloy metallographic structure, a pearlite metallographic structure and pores;

[0016] The volume percentage of the cobalt-based alloy metallographic structure is 35-40%, the volume percentage of the pores is 5-10%, and the remainder is the pearlite metallographic structure.

[0017] The volume percentage of each structure in this article includes both the endpoint value of the volume percentage range and the middle value of the volume percentage range. For example, the volume percentage of the metallographic structure of the cobalt-based alloy is 35-40%, specifically 35%, 36.5%, 38%, 39.5%, 40%, but not limited thereto.

[0018] On the other hand, the present application also provides a method for preparing a valve seat ring for a clean fuel engine, comprising:

[0019] The alloy powder is pressed into shape and then subjected to a sintering and copper-proof treatment to obtain a green body, and then the green body is re-pressed and shaped to obtain a preform, and then the preform is post-treated to obtain a valve seat ring.

[0020] The traditional valve seat manufacturing process adds copper to the alloy through a copper infiltration operation, which can effectively reduce the porosity inside the alloy material, but it will reduce the hardness of the valve seat. In order to meet the requirement of ultra-long wear resistance of the valve seat, the present application cancels the copper infiltration process, but the pores in the metallographic structure formed by the copper infiltration treatment cannot be filled, which will cause the density of the valve seat to decrease. Therefore, the present application adds a re-pressing shaping process, which can make the internal structure of the valve seat more dense, greatly reduce the surface porosity, and meet the density and crushing strength requirements of the valve seat.

[0021] In addition, the traditional valve seat ring preparation process changes the metallographic structure of the valve seat ring through deep cooling and post-tempering treatment, and can eliminate the internal stress of the material. The above-mentioned material ratio provided in the present application can obtain a specific cobalt-based alloy metallographic structure and pearlite metallographic structure after the first sintering. Therefore, the deep cooling and post-tempering treatment can be eliminated, avoiding the uneven elimination of residual stress due to improper control of the tempering treatment parameters after deep cooling treatment, which affects the wear resistance and reliability of the valve seat ring.

[0022] In one embodiment, after the green body is re-pressed and shaped, a secondary sintering and copper-free infiltration treatment is performed to obtain the preform; the temperature of the secondary sintering and copper-free infiltration treatment is lower than the temperature of the primary sintering and copper-free infiltration treatment.

[0023] The present application adds a secondary sintering process and controls the temperature of the secondary sintering copper-free treatment to be lower than the temperature of the primary sintering copper-free treatment. This not only eliminates the stress generated inside the material after the re-pressing and shaping, but also achieves the effect of grain refinement and structural homogenization inside the material, and can further improve the crushing strength and wear resistance of the valve seat ring.

[0024] In one embodiment, the temperature of the first sintering copper-impregnating treatment is 1100-1120° C., and the temperature of the second sintering copper-impregnating treatment is 990-1020° C. Thus, it can be ensured that the alloy material can form a cobalt-based wear-resistant alloy phase and a pearlite metallographic structure.

[0025] The temperature of each process in this article includes both the end value of the temperature range and the middle value of the temperature range. For example, the temperature of the first sintering copper infiltration treatment is 1100-1120°C, specifically 1100°C, 1105°C, 1110°C, 1118°C, 1120°C, but not limited to this.

[0026] In one embodiment, the time for the first sintering and copper-proof treatment is 270-300 minutes, and the time for the second sintering and copper-proof treatment is 210-240 minutes.

[0027] The time of each process in this article includes both the endpoint value of the time range and the middle value of the time range. For example, the time of a sintering copper-free treatment is 270-300 minutes, and can be specifically 270 minutes, 275 minutes, 280 minutes, 285 minutes, and 300 minutes, but is not limited thereto.

[0028] In one embodiment, the pressure of the re-pressing shaping is greater than the pressure of the pressing shaping, thereby ensuring that a denser valve seat ring is obtained after the re-pressing shaping to reduce the porosity.

[0029] In one embodiment, the pressure of the composite shaping is 150-160 t, and the pressure of the pressing molding is 50-60 t.

[0030] The pressure of each process in this article includes both the end value of the pressure range and the middle value of the pressure range. For example, the pressure of the re-pressing shaping is 150-160t, which can be 150t, 152t, 155t, 158t, 160t, but not limited to this.

[0031] In one embodiment, the compaction density of the green body after the re-pressing and shaping is 7.5-8.3 g / cm 3 .

[0032] The compaction density of each formed workpiece herein includes both the end value of the compaction density range and the middle value of the compaction density range. For example, the compaction density of the green body after the re-pressing and shaping is 7.5-8.3 g / cm 3 , specifically 7.5g / cm 3 , 7.7g / cm 3 、7.9g / cm 3 , 8.0g / cm 3 、8.3g / cm 3 , but it is not limited to this.

[0033] In another aspect, the present application provides an engine, comprising any of the above-mentioned clean fuel engine valve seat rings or a clean fuel engine valve seat ring prepared by any of the above-mentioned methods for preparing a clean fuel engine valve seat ring.

[0034] On the other hand, the present application also provides a car, comprising the engine described above.

[0035] The technical solution provided by this application can achieve the following beneficial effects:

[0036] The present application provides a clean fuel engine valve seat ring and a preparation method thereof, an engine and a car. By using two heavy metals, Co and Mo, as main components, limiting the total content of the two heavy metal components, Co and Mo, to no more than 40% of the total content and no less than 33% of the total content, and limiting the total content of all heavy metal components in the valve seat ring except iron to no more than 45% of the total content, a larger cobalt-based wear-resistant alloy phase can be produced, thereby improving the wear resistance of the valve seat ring and ensuring the sealing reliability of the valve seat ring. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 It is a data chart of the wear resistance test results of the valve seat rings prepared in Examples 1-2 of the present application and Comparative Examples 1-2.

[0038] Figure 2 This is a metallographic structure diagram of the valve seat ring prepared in Example 1 of the present application.

[0039] Figure 3 This is a metallographic structure diagram of the valve seat ring prepared in Comparative Example 1 of the present application.

[0040] Figure 4 This is a metallographic structure diagram of the valve seat ring prepared in Comparative Example 2 of the present application. DETAILED DESCRIPTION

[0041] The technical solution of the present application will be described in detail below in conjunction with the accompanying drawings.

[0042] Here, the technical solutions in the embodiments (or "implementation methods") of the present application will be described clearly and completely in conjunction with the accompanying drawings. When the following description refers to the drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements.

[0043] If there are terms involving directional indications or positional relationships in the embodiments of the present application (such as up, down, left, right, front, back, inside, outside, top, bottom, center, vertical, horizontal, longitudinal, transverse, length, width, counterclockwise, clockwise, axial, radial, circumferential, etc.), such terms are only used to explain the relative positional relationship, movement, etc. between the components under a certain specific posture (as shown in the accompanying drawings); if the specific posture changes, the directional indication or positional relationship will also change accordingly. In addition, the terms "first" and "second" in the embodiments of the present application are only used for the purpose of convenience of description and cannot be understood as indicating or implying relative importance.

[0044] Example 1

[0045] (1) Pressing: The alloy powder (excluding Cu) is mixed evenly according to the following ratios: C: 1%, Co: 28%, Mo: 8%, Cr: 2%, W: 0.5%, V: 0.15%, Mn: 0.6%, S: 0.5%, Si: 1.1%, Sn: 0.9%, impurities < 5%, and the balance is Fe. The mixture is loaded into a valve seat ring mold and the alloy powder in the mold is pressed using a press. The pressure during the pressing process is 60 tons and the pressing time is 1 min.

[0046] (2) One-time sintering without copper infiltration: The pressed green body is placed in a continuous sintering furnace, heated to 1100°C in a nitrogen atmosphere and sintered for 270 minutes to obtain the green body.

[0047] (3) Re-pressing and shaping: After the green body is naturally cooled at room temperature, it is pressed at a pressure of 160t for 7 minutes to obtain an intermediate.

[0048] (4) Secondary sintering to prevent copper infiltration: The intermediate body after re-pressing and shaping is placed in a sintering furnace. Under the conditions of nitrogen as a protective atmosphere and hydrogen as a reducing atmosphere, the temperature is raised to 1000°C and sintered for 210 minutes to obtain a preform.

[0049] (5) Post-processing: The preform is cut by mechanical processing to obtain a valve seat ring product, and then the valve seat ring product is immersed in anti-rust oil to allow the anti-rust oil to fully penetrate into the pores and surface of the valve seat ring product. Finally, the valve seat ring is prepared. The metallographic structure of the valve seat ring inside is observed by a metallographic microscope. Figure 2 shown.

[0050] Example 2

[0051] The difference from Example 1 is that the alloy powder (excluding Cu) is modified to the following proportions: C: 1%, Co: 17%, Mo: 5%, Cr: 2%, W: 0.5%, V: 0.15%, Mn: 0.6%, S: 0.5%, Si: 1.1%, Sn: 0.9%, impurities <5%, and the balance is Fe. Other experimental conditions and experimental parameters are the same as those in Example 1.

[0052] Comparative Example 1

[0053] (1) Pressing: The alloy powders were mixed evenly in the following proportions: C: 1%, Mo: 2.45%, Cr: 1.94%, Cu: 19.02%, W: 3.04%, V: 1.57%, Mn: 0.45%, S: 0.5%, impurities ≤ 2%, and the balance Fe. The mixture was loaded into a valve seat ring mold and the alloy powders in the mold were pressed using a press. The pressing pressure was 60 tons and the pressing time was 1 min.

[0054] (2) Sintering and copper infiltration: The pressed green body is placed in a sintering furnace, heated to 1100°C in a nitrogen atmosphere, and sintered for 270 minutes. During the sintering process, the copper powder contacts the green body, allowing the copper to infiltrate into the pores of the green body to obtain the green body.

[0055] (3) Deep cold tempering: The alloy product after sintering and copper infiltration is placed in a liquid nitrogen tank of a deep cold equipment and deep cooled at -150°C for 60 minutes to change the microstructure of the alloy. Then it is placed in a tempering furnace for tempering at a temperature of 550°C and a tempering time of 120 minutes to obtain a preform.

[0056] (5) Post-processing: The preform is cut by mechanical processing to obtain a valve seat ring product, and then the valve seat ring product is immersed in anti-rust oil to allow the anti-rust oil to fully penetrate into the pores and surface of the valve seat ring product. Finally, the valve seat ring is prepared. The metallographic structure of the valve seat ring inside is observed by a metallographic microscope. Figure 3 shown.

[0057] Comparative Example 2

[0058] The difference from Comparative Example 1 is that the alloy powder is modified to the following ratios: C: 1%, Co: 28%, Mo: 8%, Cr: 2%, W: 0.5%, V: 0.15%, Mn: 0.6%, S: 0.5%, Si: 1.1%, Sn: 0.9%, impurities < 5%, the balance is Fe, and Cu element is not included. The other experimental conditions and experimental parameters are the same as those of Comparative Example 1. The metallographic structure diagram of the prepared valve seat ring is as follows: Figure 4 shown.

[0059] The valve seat rings prepared in Examples 1-2 and Comparative Examples 1-2 were respectively subjected to hardness tests, crushing strength tests and wear resistance tests.

[0060] (1) Hardness test: Place the valve seat ring on the workbench of the hardness tester, ensure that the valve seat ring is stable and perpendicular to the indenter, first apply a preload of 10 kgf to make the indenter contact with the surface of the valve seat ring and keep it stable, then apply a main load of 150 kgf. Unload the main load and retain the preload. Measure the depth of the indenter pressing into the valve seat ring and automatically calculate the Rockwell hardness value (HRC) using the hardness tester.

[0061] (2) Compression strength test: GB / T7314-2005 "Method for room temperature compression test of metal materials" is used for measurement.

[0062] (3) Monomer wear resistance test: The test simulates the actual running state of the engine. The seat ring is fixed on the tooling, and the valve is driven to move rapidly in a closed device to continuously impact the seat ring. The temperature is 820℃, the speed is 3000rpm, methanol fuel, and no oil lubrication conditions are used for rapid wear for 10 hours. Please refer to the results for the results. Figure 1 , Figure 1 The vertical axis represents the amount of wear, the black column in the horizontal axis represents the amount of seat ring wear, and the green column represents the amount of wear on the valve cone surface that matches the seat ring.

[0063] Table 1

[0064]

[0065] See also Figure 1, under the same single wear test of the valve seat ring, the wear amount of the methanol valve seat ring prepared by the specific formula and special process in Example 1 of the present application is only 1 / 19 of the wear amount of the ordinary valve seat ring prepared by the comparative example 1, which greatly improves the wear resistance. In Example 2, the content of the two heavy metal components Co and Mo in the alloy material is maintained at 22%, and the volume percentage of the cobalt-based wear-resistant alloy phase finally formed is relatively small. Therefore, although the wear resistance is improved to a certain extent, the improvement effect is not significant. Although the comparative example 2 adopts the specific formula of the present application, the methanol valve seat ring prepared by the ordinary process cannot exert the characteristics of the raw materials and the porosity is increased, so the wear resistance is even worse than the ordinary valve seat ring prepared by the comparative example 1.

[0066] like Figure 2 As shown, after sintering and re-pressing and shaping by using a specific formula and combining a special production process, Example 1 of the present application can produce a larger cobalt-based wear-resistant alloy phase, and the metallographic structure is mainly cobalt-based + pearlite, with fewer pores, thereby improving the wear resistance of the valve seat ring. Figure 3 As shown in Table 1, the alloy metallographic structure formed by the ordinary formula and ordinary process in Comparative Example 1 is mainly iron, and the pores are filled with copper and solid lubricants, and no wear-resistant alloy phase is produced. As shown in Table 1, the hardness, density and crushing strength of the ordinary seat ring prepared in Comparative Example 1 are also low, which cannot meet the working requirements of the clean fuel engine. Figure 4 As shown, the number of pores in the metallographic structure of the valve seat ring prepared in Comparative Example 2 will be significantly increased, and the hardness, density and crushing strength of the valve seat ring are also relatively low, which still cannot meet the working requirements of the clean fuel engine.

[0067] It should be noted that the technical solutions or technical features described in the above embodiments can be combined or supplemented with each other without causing conflicts. The scope of protection of this application is not limited to the precise structures described in the above embodiments and shown in the drawings; all modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of this application should be included in the scope of protection of this application.

Claims

1. A valve seat ring for a clean fuel engine, characterized in that: The chemical composition includes the following weight percentages: C: 0.65~1.15%, Co: 25~28%, Mo: 8~12%, Cr: 1.7~3.5%, W: 0.2~0.6%, V: 0.05~0.3%, Mn: 0.1~0.6%, S: 0.1~0.7%, Si: 0.7%~1.4%, Sn: 0.6~1.3%, impurities <5%, the balance is Fe, and Cu is not included; The valve seat ring is composed of a cobalt-based alloy metallographic structure, a pearlite metallographic structure and pores; the volume percentage of the cobalt-based alloy metallographic structure is 35-40%, the volume percentage of the pores is 5-10%, and the remainder is the pearlite metallographic structure.

2. The valve seat ring for a clean fuel engine according to claim 1, characterized in that: The chemical composition includes the following weight percentages: C: 0.65~1.15%, Co: 26.5-27.5%, Mo: 9.5~10.5%, Cr: 3~3.5%, W: 0.4~0.6%, V: 0.1~0.2%, Mn: 0.4~0.6%, S: 0.1~0.7%, Si: 0.7%~1.4%, Sn: 0.6~1.3%, impurities <5%, the balance is Fe, and Cu is not included.

3. A method for preparing a valve seat ring for a clean fuel engine as claimed in claim 1 or 2, characterized in that: include: The alloy powder is pressed and formed, and then subjected to a primary sintering and copper-proof treatment to obtain a green body, and then the green body is re-pressed and shaped, and then subjected to a secondary sintering and copper-proof treatment to obtain a preform, and then the preform is post-treated to obtain a valve seat ring; Wherein, the temperature of the secondary sintering and copper-proof treatment is lower than the temperature of the primary sintering and copper-proof treatment.

4. The method for preparing a valve seat ring for a clean fuel engine according to claim 3, characterized in that: The temperature of the first sintering copper-impermeable treatment is 1100-1120°C, and the temperature of the second sintering copper-impermeable treatment is 990-1020°C; And / or, the time of the first sintering and copper-proof treatment is 270-300 min, and the time of the second sintering and copper-proof treatment is 210-240 min.

5. The method for preparing a valve seat ring for a clean fuel engine according to claim 3, characterized in that: The pressure of the re-pressing and shaping is greater than the pressure of the pressing and shaping.

6. The method for preparing a valve seat ring for a clean fuel engine according to claim 5, characterized in that: The compaction density of the green body after the re-pressing and shaping is 7.5-8.3 g / cm 3 .

7. An engine, characterized in that: A clean fuel engine valve seat ring comprising the clean fuel engine valve seat ring as claimed in claim 1 or 2 or a clean fuel engine valve seat ring prepared by the preparation method of the clean fuel engine valve seat ring as claimed in any one of claims 3 to 6.

8. A car, characterized in that: Comprising the engine as claimed in claim 7.

Citation Information

Patent Citations

  • Valve seat ring for alternative fuel engine

    CN104630659A